Enhancing the climate risk and adaptation fact base in the Caribbean... preliminary results of the ECA study (CCRIF Grand CaymanKY, 2010)
Focuses on the impact of climate risks and change on: a country's physical infrastructure (including housing), its tourism, travel, agricultural, industrial and services sectors. Establishes baseline risk scenarios in accord with the challenges facing the Caribbean. Provides quantitative cost-benefit analyses of risk mitigation and transfer measures.
Keywords: INSURANCE